2021
DOI: 10.2478/raon-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in stage III non-small cell lung cancer patients treated with durvalumab after sequential or concurrent platinum-based chemoradiotherapy – single institute experience

Abstract: Background Chemoradiotherapy (ChT-RT) followed by 12-month durvalumab is the new standard treatment for unresectable stage III non-small cell lung cancer. Survival data for patients from everyday routine clinical practice is scarce, as well as potential impact on treatment efficacy of sequential or concomitant chemotherapy and the usage of gemcitabine. Patients and methods We retrospectively analysed unresectable stage III NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The results of this single institution retrospective analysis demonstrate that for patients with locally advanced stage III NSCLC, the use of adjuvant durvalumab after completion of chemoradiation improves PFS and OS compared to historic controls treated with chemoradiation alone. Although most patients in our trial did not conform to eligibility criteria for inclusion in the PACIFIC trial because of delay in starting adjuvant durvalumab ( n = 51), history of immune disease ( n = 3), or ECOG status ≥2 ( n = 4), the improved PFS and OS with adjuvant durvalumab observed in our study are consistent with outcomes reported in the PACIFIC trial and other real‐world studies 7–18 . The real‐world data presented in this study, although limited, suggest that future clinical trials consider inclusion of patients who begin durvalumab therapy beyond 42 days after completion of chemoradiation, have a prior history of immune disease, or have an ECOG performance status ≥2.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results of this single institution retrospective analysis demonstrate that for patients with locally advanced stage III NSCLC, the use of adjuvant durvalumab after completion of chemoradiation improves PFS and OS compared to historic controls treated with chemoradiation alone. Although most patients in our trial did not conform to eligibility criteria for inclusion in the PACIFIC trial because of delay in starting adjuvant durvalumab ( n = 51), history of immune disease ( n = 3), or ECOG status ≥2 ( n = 4), the improved PFS and OS with adjuvant durvalumab observed in our study are consistent with outcomes reported in the PACIFIC trial and other real‐world studies 7–18 . The real‐world data presented in this study, although limited, suggest that future clinical trials consider inclusion of patients who begin durvalumab therapy beyond 42 days after completion of chemoradiation, have a prior history of immune disease, or have an ECOG performance status ≥2.…”
Section: Discussionsupporting
confidence: 82%
“…Although most patients in our trial did not conform to eligibility criteria for inclusion in the PACIFIC trial because of delay in starting adjuvant durvalumab (n = 51), history of immune disease (n = 3), or ECOG status ≥2 (n = 4), the improved PFS and OS with adjuvant durvalumab observed in our study are consistent with outcomes reported in the PACIFIC trial and other real-world studies. [7][8][9][10][11][12][13][14][15][16][17][18] The real-world data presented in this study, although limited, suggest that future clinical trials consider inclusion of patients who begin durvalumab therapy beyond 42 days after completion of chemoradiation, have a prior history of immune disease, or have an ECOG performance status ≥2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“… 1 But still, nearly half of the patients will experience locoregional relapse. 2 The accuracy of different steps in radiotherapy treatment preparation and execution have a strong impact on local control. 3 With the introductionof computed tomography (CT), positron emission computed tomography (PET CT) and four-dimensional (4D) CT simulation, the target delineation accuracy increased.…”
Section: Introductionmentioning
confidence: 99%